β-Carotene gingival mucoadhesive patch on Cx-43 and 8-Oxo-dg expression to prevent micronucleus formation due to panoramic radiography exposure - Shantiningsih, Rurie Ratna; Suwaldi, Suwaldi; Astuti, Indwiani; Mudjosemedi, Munakhir (Padjadjaran Journal of Dentistry, 2019)
Introduction: β-carotene as a lipid-soluble antioxidant substance, expected to prevents the oxidative reaction and to improve the junctional communication detected by Cx-43. Micronucleus is known as one of the early markers of DNA damage which might be related to carcinogenesis mechanism that increased by panoramic radiography radiation exposure. The objective of this research was to analyse the effect of the β-carotene gingival mucoadhesive patch on Cx-43 expression and 8-oxo-dG to prevent micronucleus formation at the gingival mucosa of New Zealand rabbit due to panoramic radiography radiation exposure. Methods: β-carotene gingival mucoadhesive patch was applied to gingival mucosa of the experimental rabbits. In Group I, the rabbits without patch was a control group. Group II has applied the patch before radiography exposures, Group III during the radiography exposures, and Group IV after radiography exposures. Micronucleus samples were taken from the rabbit’s swabbed gingival mucosa, then stained using modified Feulgen-Rossenbeck. The 8-oxo-dG and Cx-43 expressions were detected using immunohistochemistry technique. The results were then analysed using two-way ANOVA. Results: The increasing number of micronucleus in Group I had a different mean (p < 0.05) with Group III and IV. The expression of 8-oxo-dG and Cx-43 had significant differences (p < 0.05) between Group I and III. This results indicated that β-carotene gingival mucoadhesive patch prevents the increasing number of micronucleus especially when it applied before and during panoramic radiography radiation exposure by the increasing Cx-43 and decreasing 8-oxo-dG expression. Conclusion: The β-carotene gingival mucoadhesive patch can be utilised to prevent the panoramic radiography radiation exposure’s effect. Keywords: β-carotene, gingival-mucoadhesive patch, micronucleus, radiation exposure